Development Status and Application Prospect of Domestic Tram - HAN Zhibin; LI Fu; HUANG Yunhua (机车电传动)
The development course of the tram was briefly described, the research and development status and technical characteristics of tram of the domestic rail vehicle suppliers were summarized, the functional orientation and adaptation conditions of the tram were analyzed, suggestions were put forward on the development of trams in domestic cities, and thinks that we should construct the trams scientifically and rationally.